2020
DOI: 10.5222/shyd.2020.65807
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Of Competence Status Of Intern Nurses’ Attitudes Towards To Their Caregiver Roles

Abstract: INTRODUCTION: The study was conducted to examine the relationship between the competence status of the intern nurses and their attitudes towards to their caregiving roles. METHODS: This descriptive and correlational study was carried out with 295 students who studied in nursing department of an university between March and April 2019. Data were collected by using the Student Information Form, the Competence Scale of Nursing Students and the Attitude Scale for Nurses in Caregiving Roles. The data were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…Similar to the findings of this study, as a result of the studies in the literature in which the professional competencies of senior nursing students were assessed using the same measurement tool (CINS), it was observed that the students evaluated their own professional competency levels as good and they felt more competent in the fields of critical thinking-reasoning, lifelong learning, ethics, and accountability (Çelik et al, 2020;Hsu & Hsieh, 2013). Public health nursing class covers giving information and improving skills on caregiving in a process from improving health to rehabilitation in all areas where individuals of all ages, families, the public live, and work.…”
Section: Case-subject Interactionsupporting
confidence: 84%
“…Similar to the findings of this study, as a result of the studies in the literature in which the professional competencies of senior nursing students were assessed using the same measurement tool (CINS), it was observed that the students evaluated their own professional competency levels as good and they felt more competent in the fields of critical thinking-reasoning, lifelong learning, ethics, and accountability (Çelik et al, 2020;Hsu & Hsieh, 2013). Public health nursing class covers giving information and improving skills on caregiving in a process from improving health to rehabilitation in all areas where individuals of all ages, families, the public live, and work.…”
Section: Case-subject Interactionsupporting
confidence: 84%
“…Students who do not experience caring behaviors may experience feelings such as depression, stress and anxiety. These feelings may hinder learning and prevent them from performing their nursing skills (11,21). Caring behaviors can only be supported by generations who experience and have positive feelings for care (2).…”
Section: Discussionmentioning
confidence: 99%
“…Teorik eğitim, klinik deneyimler, rol model alınan eğiticiler ve hemşireler, hemşirelik öğrencilerinin mesleki değerleri algılama düzeyini ve bakım verici rollerine ilişkin tutumlarını etkileyen önemli faktörlerdir. [17][18][19] Lisans eğitimi sürecinde eğitim ve danışmanlığın, hemşirelik öğrencilerinin mesleki değerleri ile bakım verici rollerine etkisinin belirlenmesi amacıyla 137 öğrenci ile dört yıllık boylamsal desenli olarak yapılan bu çalışmada, deney ve kontrol gru-bundaki öğrencilerin bakım verici rollerine ilişkin tutumlarının ve mesleki değerleri algılama düzeylerinin dört yılda artış gösterdiği saptanmıştır. Deney ve kontrol gruplarının bakım verici rollerine ilişkin tutumları arasında istatistiksel olarak anlamlı fark saptanmamıştır.…”
Section: Discussionunclassified
“…Bakım verici rolü, bu rollerden sadece biri olup bireylerin fizyolojik ve psikolojik gereksinimlerine yardımcı olmaya ilişkin faaliyetleri gerçekleştirirken bireylerin onurlarını korumayı da içerir. 19 Literatürde yapı- 17 Subke ve ark., destekleyici, motive edici, öğretici ve cesaretlendirici bir klinik öğrenme ortamının hemşirelik öğrencilerinin bakım uygulamalarını olumlu yönde geliştireceğini belirtmektedir. 18 Birimoğlu ve Ayaz'ın çalışmasında, birinci sınıftan dördüncü sınıfa kadar izlenen hemşirelik öğrencilerinin bakım davranışlarını sıklıkla uyguladıkları saptanmıştır.…”
Section: Discussionunclassified